PERANCANGAN DAN PENDAMPINGAN PENGELOLAAN SURAT BERBASIS KEBUTUHAN - Suryani, Nanik; Ismiyati, Ismiyati; Jaenudin, Ahmad (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2019)
The aim of devotion is (1) designing the letter management basedon need analysis of school; (2) training in implementing the result of design; (3) arranging the classification of archive; and (4) implementing the electronic letter management. The main priority of devotion is providing knowledge about handling of incoming and outgoing letter. In addition, the dedication is realizing to create the good administration for school, so that it can be supporting the accountability of school with authentic document. The implementation of devotion through socialization and training about management of letter based on need analysis. To overcome the obstacles of implemention in handling letter, we would evaluate from mentoring activity.